TROUBLED FIRMS IN INDONESIA STOCK EXCHANGE: THE MONITORING ROLE OF AUDIT COMMITTEE - Syahriar Abdullah; Istinganah Eni Maryanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Given the significant number of troubled firms in Indonesian Stock Exchange in recent years, this study aims to examine the role of the audit committee in helping Indonesian listed firms to overcome various problems. We analyse secondary data from troubled firms in Indonesia Stock Exchange for 2018-2020 using ordered logistic regression. From our examination, there are several Indonesian listed firms were given special notation in IDX website, dominated with financial reporting problems, followed with financial problems, and legal compliance problems. We also find that audit committee expertise, activities, and meeting attendance hold significant monitoring role in helping firms avoid accountability problems, proven with significant negative effect. This research contributes to answering the limitations of the literature on issues of issuers' study on the Indonesia Stock Exchange so that it plays a role in enriching the existing literature with a comprehensive investigation of the role of the audit committee. This research also contributes to providing recommendations for the practice of audit committees in order to realize an accountable company that is free from various problems, both financial, legal, and financial reporting issues.